Polyarteritis nodosa and drug abuse: is there a connection?. Issue 853 (November 1996) - Samuels, N.; Shemesh, O.; Yinnon, A. M.; Fisher, D.; Abraham, A. S.
Abstract : Drug abuse has been controversially linked to polyarteritis nodosa. A 28-year-old man with a history of drug abuse with inhaled heroin presented with an enigmatic illness consisting of refractory fever, bilateral pleural effusions, migratory polyarthritis, and a leukaemoid reaction. An abdominal angiography confirmed the diagnosis of polyarteritis nodosa, and treatment with both prednisone and cyclophosphamide resulted in significant clinical and laboratory improvement.